System Dynamics Usage in The Development of Sustainable Fishermen Village A Capability Enhancement to the Policy Review and Implementation Team in Ministry of Marine Affairs and Fisheries - Basbeth, Firdaus; Savitry, Gusti Ayu Made; Putri, Nanda Alifia (Sekolah Tinggi Manajemen IPMI, 2023)
The Ministry of Maritime Affairs and Fisheries (KKP) through the Biak Numfor Regency Fisheries Service, is developing Samber-Binyeri Village, as a pilot fishing village in Papua to enhance the economy. A number of issues and factors, including inadequate fishing equipment, infrastructure, availability of fuel, and a lack of knowledge and skills on fishing technology and practice, have contributed to the low income and productivity of traditional fishermen. Furthermore, poor health facilities and coastal waste management make the villages unhygienic to live in, messy, and unattractive for visitors and tourists. However, implementing new policies and management practices requires a proper understanding of current practice, culture, and its impact on its ecosystem, should the change be made. Therefore, it requires proficient teams to evaluate the current model and develop a new model that yields exemplary outcomes aligned with the objectives at minimum risk. For this reason, equipping the KKP team with knowledge related to system thinking and system dynamics is very important. A four-day' workshop in system thinking and system dynamics has been carried out in Bandung in two stages: stage one, a basic understanding of system thinking and system dynamics, and stage two, modeling optimization using Vensim software. The output of this workshop programs is: to define problems and dynamic hypotheses in each field or section as a basis for Sustainable development of Kampung Nelayan Maju